Complex karyotypes in hematologic disorders: a 12-year single-center study from Lebanon - Rammal, Souraya; Abou Abdallah, Farid; Attieh, Charbel; El Mounajjed, Zeinab; Semaan, Warde; Chebly, Alain (Frontiers in Oncology, 2024)
Conventional cytogenetic analysis is an important tool for the diagnosis of many hematologic disorders (HD). A karyotype is designed as « complex » when several alterations are detected. However, there is no clear consensus on the exact definition of a complex karyotype (CK), and there is a lack of studies that exclusively analyze CK in the literature. Complex karyotypes were analyzed over a period of 12 years at the Jacques Loiselet Center for Medical Genetics and Genomics (CGGM) at Saint Joseph University in Beirut (USJ) in Lebanon. 255 CK were analyzed with their associated chromosomal abnormalities (CA) detected. Out of 255 patients, 59.22% were males with a mean age of 59 years. The most common anomaly associated with CK was hyperdiploidy with a prevalence of 22.41%, which is different from a previously published study. To our knowledge, this represents the largest series of CK, particularly within the Middle East region. This study underscores the critical role of conventional cytogenetics in detecting CK, ultimately contributing to improved management of HD. Further investigations focusing on CK are needed.